Perceptions of challenges and strategic interventions for managing transboundary lumpy skin disease: The path forward in Malaysia - Nabilah Abd Talib; Syamira Syazuana Zaini; Mark Buda; Norhariani Mohd Nor (Jurnal Medik Veteriner, 2026)
Lumpy Skin Disease (LSD) has emerged in Malaysia in recent years, causing significant economic losses and raising industry concerns. With limited data on the local outbreak's impact, this qualitative study investigates the challenges faced by the Malaysian ruminant industry during the 2021–2022 outbreak. Using purposive focus group interviews, the study targeted key government officials to identify challenges and propose strategic interventions for disease management. The findings provide valuable insights for future improvements. A total of 20 responses were successfully analyzed using thematic analysis, yielding three main themes with eight subthemes related to LSD challenges, and four themes with nine subthemes representing multifactorial strategic intervention approaches. Thematic analysis revealed multifactorial challenges and control strategies for LSD: (i) knowledge gaps in disease emergence, (ii) systemic and socio-economic barriers to effective LSD control, and (iii) governance and policy limitations, including issues related to culling policies and inadequate border control. The multifaceted approaches to controlling LSD include improving decision-making and response times, establishing emergency preparedness guidelines such as training and simulation exercises, and enhancing surveillance and investigation strategies. The findings are based on expert opinions from government officials, which may limit the discussion to regulatory improvements. Future research at the farm level could provide more comprehensive insights for LSD management. Overall, the study’s findings can inform the development of standard operating procedures for LSD management, supporting better decision-making and budget allocation in the ruminant industry.